2011
DOI: 10.1042/cs20110151
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular adipose tissue: more than just structural support

Abstract: The perivascular adipose tissue (PVAT) has recently been recognized as a novel factor in vascular biology, with implications in the pathophysiology of cardiovascular disease. Composed mainly of adipocytes, PVAT releases a wide range of biologically active molecules that modulate the vascular smooth muscle cell contraction, proliferation and migration. PVAT exerts an anticontractile effect in various vascular beds which seems to be mediated by yet elusive PVAT-derived relaxing factor or factors (PVRF). Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
0
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 101 publications
(160 reference statements)
3
160
0
18
Order By: Relevance
“…Their paracrine effects might be attributable to their location being close to the adventitia and extravascular bed [14][15][16] Gastaldelli et al 16 reported the existence of a link between EAT and hypertension, atherosclerosis, and coronary heart disease. Nakanishi and colleagues 17 reported that increased epicardial fat volume measured by CT is associated with greater progression of coronary artery calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Their paracrine effects might be attributable to their location being close to the adventitia and extravascular bed [14][15][16] Gastaldelli et al 16 reported the existence of a link between EAT and hypertension, atherosclerosis, and coronary heart disease. Nakanishi and colleagues 17 reported that increased epicardial fat volume measured by CT is associated with greater progression of coronary artery calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Perivascular adipocytes (PVA) deliver substantial quantities of metabolically dynamic substances with both endocrine and paracrine actions [19]; PVA of human internal thoracic artery release NO [20]; PVA discharges nicotinamide adenine dinucleotide phosphateoxidase in mice [21]; rat PVA discharge compliment [23,22]; rat PVA discharge metylpalmitate ester [23]; different substances, for example, plasminogen activator inhibitor-1 and interleukin-6 are contained in epicardial adipose tissue in patients with acute coronary syndrome [24]; cultured human epicardial adipose tissues release glutation S-transferase P and ApoA1 [25]. But, reports depicting release and storage of lipoproteins from human PVA, including PCAT, to the nearby vessel wall were not found.…”
Section: Other Reportsmentioning
confidence: 99%
“…O tecido adiposo perivascular (TAP) é diferente de outros tecidos adiposos, por causa de sua localização ao redor da maior parte dos vasos sanguíneos, com exceção da circulação cerebral 59 . Ainda não é muito bem estabelecido se o TAP é um tecido adiposo branco, bege, marrom ou outro tipo de tecido adiposo 60 , embora haja evidências para se acreditar que seja tecido adiposo branco.…”
Section: Tecido Adiposo Perivascularunclassified
“…Ainda não é muito bem estabelecido se o TAP é um tecido adiposo branco, bege, marrom ou outro tipo de tecido adiposo 60 , embora haja evidências para se acreditar que seja tecido adiposo branco. O TAP possui um contato direto com a camada adventícia 61 e com o vasa vasorum 59 . Muitas vezes o TAP infiltra na camada adventícia.…”
Section: Tecido Adiposo Perivascularunclassified
See 1 more Smart Citation